A Predatory West, Africa’s Postcolonial States, International Trade Relations and Underdevelopment in Africa: A Survey of Centre/Core-Periphery Issues - Masumbe, Peter Sakwe (Advances in Social Sciences Research Journal, 2024)
This paper examines a predatory West and Africa’s postcolonial states international trade relations and underdevelopment in Africa to divulge how centre-periphery issues evoke underdevelopment in postcolonial African states. It argues that, historically, be it a core or peripheral, in whatever mode of production, the state is the dominant laboratory for all human activities, as it plays ever-dominant roles in domestic and international politico-economic and socio-cultural affairs, being the primary vector for development or underdevelopment is society. However, international trade relations have conditioned these roles and capacities of the state, in terms of strengths or weaknesses in service delivery to its citizens. Having been incorporated and monetised into the West’s capitalism, the postcolonial Africa’s state, has despite these roles, subjectively occupied a debilitating peripheral capitalist position in global wealth production. Today, like yesterday, the postcolonial African state, exhibits excruciating and traumatising underdevelopment, incarnated by uncivilised political, social, economic infrastructures, which incubate citizens’ apathy to governance, while enhancing insecurity, poverty, conflicts and fragmentation of nationalities. Using Raul Prebisch’s (1949) dependency theory, I argue that, the weaknesses and fragilisation of the postcolonial African state accrue from the despondent peripheral capitalist position it occupies in the international capitalist division of labour. Via Wallenstein’s (1930-2019) Modern World System theory, (MWS), I seek reawakening the gratuitous Africans’ slumbering consciousness towards overcoming underdevelopment; impelled by a predatory West’s instigated peripheral capitalism.